Intelligence Concept: A Cross-cultural Study of University Students from The Javanese and Madurese in East Java - Agung Minto Wahyu; Angger Pangestu; Retno Sulistiyaningsih; Ninik Setiyowati (Institut Agama Islam Negeri Madura, 2021)
Intelligence is often used as a benchmark to predict someone's success in the future. Therefore, intelligence is also often used as a reason for someone to label individuals who do not have the abilities that others want. Students of education faculty as prospective educators in the future have a fairly central role in providing understanding about the intelligence that students have to the parents, senior teachers, and students themselves. Before becoming an educator, education students are expected to have a good concept of intelligence so that the understanding given can be done precisely. This study aims to reveal the concepts of intelligence subjectively to the students of prospective educators from the Javanese and Madurese. The study used a qualitative research approach with a case study model that emphasized the exploration of a system that intertwined with each other. The results showed that education students who originated from Javanese and Madurese have a very diverse concept of intelligence. Despite the diverse concept of intelligence, the concept of the student intelligence of both tribes has a relation that complements each other. Students of both tribes also have the view that each individual has different intelligence. Therefore, most of the students from both tribes have been in line with Howard Gardner’s multiple intelligences theory. The findings in this study are that interpersonal intelligence is considered to be the most prominent by the Madurese people, because the ability to connect with others is very high.